Las dos caras de una ciudad: planificación y segregación urbana en el barrio de Monserrate - Grijalva Flores, Emil Faryd (2024)
This essay makes a critical analysis of the management of the Historic Center of Lima (CHL) through the Management of Planning, Management and Recovery of the Historic Center of Lima (PROLIMA) and its impact on urban segregation. It explores how policies focused on heritage conservation and tourism have led to an unequal distribution of attention and resources among the neighborhoods of the CHL, with special emphasis on the case of the Monserrate neighborhood. Despite its historical and cultural richness, Monserrate has been marginalized in terms of municipal investment and attention, resulting in significant deterioration of its infrastructure and high vulnerability to natural disasters. This essay reveals that PROLIMA’s interventions prioritize areas with greater tourism potential, leaving Monserrate and other similar neighborhoods in a state of neglect. This inaction is categorized as segregation by default, a perspective that explains how the deliberate or negligent omission of inclusive policies perpetuates the exclusion and marginalization of certain neighborhoods. The essay concludes that urban policies in Lima’s Historic Center have favored the restoration of monuments and cultural tourism, relegating neighborhoods such as Monserrate and perpetuating socio-spatial segregation. The effectiveness of the Master Plan for the Historic Center of Lima (PMCHL) is questioned due to the lack of citizen participation, which has disconnected urban policies from everyday realities. In addition, neighborhood resistance in Monserrate is highlighted as a response to municipal negligence and exclusion, highlighting the residential character that this area still possesses.